2010
DOI: 10.1016/j.bbrc.2010.10.066
|View full text |Cite
|
Sign up to set email alerts
|

The mammalian INO80 complex is recruited to DNA damage sites in an ARP8 dependent manner

Abstract: Dynamic changes in chromatin structure are essential for efficient DNA processing such as transcription, replication, and DNA repair. Histone modifications and ATP-dependent chromatin remodeling are important for the alteration of chromatin structure. The INO80 chromatin remodeling complex plays an important role in HR-mediated repair of DNA double-strand breaks (DSBs). In yeast, the INO80 complex is recruited to the sites of DSBs via direct interaction with phosphorylated histone H2A and facilitates the proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 28 publications
1
38
0
Order By: Relevance
“…We found that both γ-H2AX and 53BP1 efficiently localized to IR-induced DSBs and to dysfunctional telomeres in mIno80 ∆/∆ MEFs, suggesting that mIno80 is not required for the accumulation of γ-H2AX and 53BP1 at DNA damage sites. As the mammalian mINO80 complex lacks Nhp10, this species-specific difference likely renders it dispensable for interacting with γ-H2AX at DSBs [21,24,59]. Rather, mammalian INO80 appears to require its Arp-8 subunit for recruitment to laser-induced DSBs [59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that both γ-H2AX and 53BP1 efficiently localized to IR-induced DSBs and to dysfunctional telomeres in mIno80 ∆/∆ MEFs, suggesting that mIno80 is not required for the accumulation of γ-H2AX and 53BP1 at DNA damage sites. As the mammalian mINO80 complex lacks Nhp10, this species-specific difference likely renders it dispensable for interacting with γ-H2AX at DSBs [21,24,59]. Rather, mammalian INO80 appears to require its Arp-8 subunit for recruitment to laser-induced DSBs [59].…”
Section: Discussionmentioning
confidence: 99%
“…As the mammalian mINO80 complex lacks Nhp10, this species-specific difference likely renders it dispensable for interacting with γ-H2AX at DSBs [21,24,59]. Rather, mammalian INO80 appears to require its Arp-8 subunit for recruitment to laser-induced DSBs [59]. IR-and UV-induced DNA damages persist in mIno80 ∆/∆ MEFs, suggesting that mIno80 is required for their efficient repair (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Several chromatin-remodelling proteins are implicated in the efficient repair of DNA damage in mammalian cells, including BRG1, CHD1L/ALC1, CHD4, INO80 and ISWI proteins ACF1 and SNF2H (Ahel et al, 2009;Kashiwaba et al, 2010;Lan et al, 2010;Larsen et al, 2010;Lee et al, 2010;Nakamura et al, 2011;Park et al, 2009;Park et al, 2006;Polo et al, 2010;Sánchez-Molina et al, 2011;Smeenk et al, 2010). Most of the chromatinremodelling proteins are recruited to DNA breaks in a cH2AX-dependent manner and function to modulate chromatin structure and modifications in order to facilitate the access to either DNA or chromatin of factors involved in DNA damage signalling and repair.…”
Section: Discussionmentioning
confidence: 99%
“…For example, ARP4, ARP5 and ARP8, together with actin, form subunits of the mammalian INO80 chromatin-remodelling complex that functions in transcriptional regulation, DNAdamage-induced double strand break repair and the nucleotide excision repair (NER) pathway (Jin et al, 2005;Jiang et al, 2010). ARP8 is required for the recruitment of mammalian INO80 to sites of DNA damage (Kashiwaba et al, 2010), and ARP5 has been shown to have a specific role in the INO80-mediated NER pathway in response to UV lesions (Jiang et al, 2010). Moreover, ARP5 enhances the accumulation of phosphorylated histone H2AX, which might be required for the recruitment of repair factors (Kitayama et al, 2009).…”
Section: Nuclear Arp Proteinsmentioning
confidence: 99%